PENTINGNYA PENDIDIKAN KARAKTER KRISTEN DI ERA MODERNISASI DAN APLIKASINYA BAGI PESERTA DIDIK DI SMA KRISTEN ADI WIYATA JEMBER - Dian Santayu Gulo (Metanoia, 2022)
Students in this case Adolescents today are growing and developing with a great dependence on digital technology, so it is not surprising that at a very young age they are so skilled at it. Today's youth are growing with the advancement of digital technology in an instant and egocentric world. Education is a human effort to develop and develop innate potentials, both physically and spiritually in accordance with the values that exist in society and culture. Christian characters are traits attached to a person's personality. While Christianity is a term for someone who has accepted Jesus Christ as Lord and Savior in person, as well as imitating his life and teachings in daily life. Thus, the Christian character is also called Christian traits, namely the spiritual qualities that a Christian has. Responsibility is the attitude and behavior of a person to carry out their duties and obligations as he should do to oneself, society, environment, country and God Almighty. Loyalty is a strong feeling about someone's support and perseverance that shows full and continuous support. Love / Care is love is a good deed done by someone for others by sacrificing or answering people's needs.